UNIVERSITY SPORTS CLUBS AS A TOOL FOR STUDENT ENGAGEMENT: A COMPARATIVE STUDY OF UZBEKISTAN AND INTERNATIONAL PRACTICES (Eureka Journal of Physical and Chemical Research, 2026)
This review article examines the role of university sports clubs as an effective instrument for enhancing student engagement, with a particular focus on the comparative analysis of Uzbekistan and international practices. Drawing on a wide range of scholarly literature, policy documents, and empirical studies, the paper explores the organizational, social, and pedagogical functions of sports clubs within higher education systems. In many developed countries, university sports clubs are deeply integrated into institutional structures, contributing not only to students’ physical well-being but also to their socialization, leadership development, and sense of belonging. In contrast, the system of university sports clubs in Uzbekistan is still in a stage of transformation, characterized by limited institutional autonomy, insufficient funding mechanisms, and a lack of structured management models.
Keywords: University sports clubs; student engagement; higher education; Uzbekistan; comparative analysis; student sport; club system; physical activity; sports management; international practices